Clinical utilization of magnetic resonance enterography in small bowel Crohn's disease management: a retrospective tertiary centre experience. Issue 7 (31st July 2020) - Yip, Alexander; Croese, Alexander; Vangaveti, Venkat; Sidhu, Ankur; Lam, David; Woods, Rodney; D'Souza, Basil
Abstract: Background: Magnetic resonance enterography (MRE) is the mainstay imaging modality in the evaluation of small bowel Crohn's disease (CD) activity and its associated complications. Few studies have assessed the indications for ordering it and its association with management changes. The objective was to identify the current clinical utilization of MRE and associated management changes in patients with established small bowel CD. Methods: A retrospective audit was conducted on all patients with established CD who underwent MRE at a tertiary centre from November 2014 to December 2017. Clinical indications, radiological findings and management changes were obtained from patient records. Results: A total of 220 patients underwent a total of 287 MRE examinations. The most common indications for ordering MREs were based on patient symptoms ( n = 204, 71.1%) and routine disease surveillance ( n = 57, 19.9%). The most common radiological findings were inflammation ( n = 156, 54.4%) and strictures ( n = 98, 34.1%). Management changes post MRE occurred in 152 of 287 (53%) cases. Of the 152 patients, 87 (57.2%) had changes in medical management, 40 (26.3%) had surgical or endoscopic intervention and 25 (16.4%) had both medical and surgical management changes. Management changes following MRE in patients with new or concerning symptoms were significantly higher than in surveillance patients (OR 4.1, P = 0.000003). Conclusion: This study provides a foundation for understanding the current utilization of MRE in small bowel CD at a tertiary centre. However, its role in altering management particularly within surveillance patients is yet to be defined. Future prospective trials are required to better delineate its role and develop an algorithm for small bowel CD management. Abstract : Magnetic resonance enterography (MRE) has become the mainstay imaging modality for assessing patients with small bowel Crohn's disease. Understanding the clinical indications for ordering MRE in these patients is important in guiding clinician decision‐making. This study highlights the current utilization and radiological findings of MRE in Crohn's disease at a quaternary inflammatory bowel disease centre, particularly in surveillance patients.